PENGARUH ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA), ARUS KAS OPERASI DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM (STUDI KASUS PADA PERUSAHAAN INDEKS LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA) - FEVIN ANDRYANTO; WIDARTO RACHBINI; JMV MULYADI (LP2MTBM MAKARIOZ, 2021)
This study aims to examine empirical evidence related to the analysis of the relationship between Economic Value Added(EVA), Market Value Added (MVA), Operating Cash Flow Earning Per Share (EPS) on Stock Returns in LQ 45 IndexCompanies listed on the Indonesia Stock Exchange for the period 2012 -2016.. Methods for collecting the required data werecollected using documentation techniques (desk research), with a total sample of 20 companies. The data analyzed in thisstudy were compiled from annual reports and company financial statements. The analytical technique used is descriptiveanalysis and panel data with the Eviews 9 program. The results show that Economic Value Added (EVA) and Market ValueAdded (MVA) have a positive and significant effect on Stock Returns, Operating Cash Flow (AKO) and Earning Per Share( EPS) has no effect on stock returns.